Odpowiedzi

2010-01-04T18:08:00+01:00
A)
y=-2x-1
x=y+7

y=-2(y+7)
y=-2y-14
3y=-14
y=-14/3=-4 1/3
x=4 1/3+ 7=11 1/3
y=-4 1/3
x=11 1/3
b)
-3x=2y
y=1-x
-3x=2(1-x)
-3x=2-2x
-x=2
x=-2
y=1-x
y=1+2
y=3
x=-2
c)
x+y=0
x-y=10
x=-y
-y-y=10
-2y=10
y=-5
x+y=0
x-5=0
x=5
y=-5
d)
8x-6y=10
7x+y=5
y=5-7x
8x+6(5-7x)=10
8x+30-35x=10
-27x=-20
x=20/27
y=5-7(20/27)
y=5-(5 5/27)
y=5-140/27
y=-5/27
x=20/27
Pozdro, chyba się nie machnąłem nigdzie :)
1 5 1
2010-01-04T18:11:11+01:00
A) y=-2x-1
x=y+7

y=-2*(y+7)-1
x=y+7

x=y+7
y=-2y-14-1

x=y+7
y+2y=-15

x=y+7
3y=-15/3

x=y+7
y=-5

y=-5
x=2

b)-3x=2y
y=1-x

y=1-x
-3x=2*(1-x)

y=1-x
-3x=2-2x

y=1-x
-3x+2x=2

y=1-x
-x=2/*(-1)

x=-2
y=1-2=-1

c)x+y=0
x-y=10

x+y=0
x=10+y

x=10+y
10+y+y=0

x=10+y
2y=10/2

y=5
x=10+5=15

d)8x-6y=10
7x+y=5

8x-6y=10
y=5-7x

y=5-7x
8x-6*(5-7x)=10

y=5-7x
8x-30+42x=10

y=5-7x
50x=40/50

y=5-7x
x=40/50 (w ułamku)

x=40/50
y=5-7*40/50

x=40/50
y=5-280/50
1 5 1
Najlepsza Odpowiedź!
2010-01-04T18:12:03+01:00
A)
y=-2x-1
x=y+7

y=2x-1
x=2x-1+7

y=2x-1
x-2x=-1+7

y=2x-1
-x=6 /:-1

y=2x-1
x=-6

y=2*(-6)-1
x=-6

y=-13
x=-6


b)
-3x=2y
y=1-x

-3x=2(1-x)
y=1-x

-3x=2-2x
y=1-x

-3x+2x=2
y=1-x

-x=2 /:-1
y=1-x

x=-2
y=3

c)
x+y=0
x-y=10

x=-y
x-y=10

x=-y
-y-y=10

x=-y
-2y=10 /:-2

x=-y
y=-5

x=5
y=-5

d)
8x-6y=10 /:2
7x+y=5

4x-3y=5
y=5-7x

4x-3(5-7x)=5
y=5-7x

4x-15+21x=5
y=5-7x

25x=20 /:25
y=5-7x

x=0,8
y=5-7*0,8

x=0,8
y=0,6
2 5 2